Implementation of Dual Citizenship as a Result of Mixed Marriages from a Human Rights Perspective in Indonesia - Aprilia, Indah Siti; Hadiati, Mia; Januar, Akbar Putra (AURELIA: Jurnal Penelitian dan Pengabdian Masyarakat Indonesia, 2024)
The issue of determining dual citizenship for children from mixed marriages is still often debated as a matter of human rights and also justice for the parties involved. This research uses normative juridical methods. The results of the analysis show that children from mixed marriages have dual citizenship up to the age of 18 with limited registration mechanisms. Ownership of dual citizenship actually needs to be protected by each country. Indonesia itself recognizes dual citizenship up to the age of 18 years plus an extension of the legal period until the age of 21 years. For the protection of human rights, the author recommends that regular socialization and citizenship services be carried out for children from mixed marriages in a thorough and comprehensive manner.